Penerapan Metode Demonstrasi untuk Meningkatan Hasil Belajar Siswa Materi Pelajaran Pendidikan Agama Islam di SMPN 20 Mukomuko - Husain Abdurrahman; Ali Akbarjono (Jurnal Indonesia Kajian Pendidikan Islam, 2025)
The purpose of this study was to determine how much the improvement of student learning outcomes in Islamic religious education subject matter through the demonstration method. This research uses Classroom Action Research. This research was conducted at SMP Negeri 20 Mukomuko in 2023. The research subjects were first grade students totaling 18 students. Subjects were taken using purposive sampling technique. Data collection using observation and tests. Data analysis using learning completeness. The research stages include planning, acting, observing, reflecting. The results showed that demonstration method learning can improve student learning outcomes in Islamic religious education subjects. The results of this study can be used as reference material and consideration for religious teachers in order to improve student learning outcomes in Islamic religious education subject matter through demonstration methods, and can be used as a strategy in teaching activities in order to improve student learning outcomes in Islamic religious education subject matter through demonstration methods.